A new species of Geranium (Geraniaceae) from Himachal Pradesh, India - Wagh, Vijay Vishnu; Hurrah, Imtiyaz Ahmad (Phytotaxa, 2020)
Geranium lahulense, a new species from Keylong, Lahul & Spiti district of Himachal Pradesh, is described and illustrated. The new species is distinguished from its allied species (G. richardsonii, G. pratense, G. himalayense) by its deltoid-subulate stipules, polygonal to sub-globular leaves with widely separated rhombic segments, white obovate-cordate petals and mericarps without any transverse vein at apex. A morphological comparison with related species and taxonomic key to distinguish the species are also provided.